Alcohol and kidney damage: a Janus-faced relationship - Schäffner, Elke; Ritz, Eberhard (Kidney international, 2015)
It has been known for a long time that excessive consumption of alcohol has adverse effects, including adverse impact on kidneys and kidney disease. Recently, observational evidence has been provided that moderate alcohol consumption is associated with less cardiovascular and renal risk. These issues had been summarized and discussed at the recent congress of the European Society for Biomedical Research and Alcoholism in Vienna.